PENGEMBANGAN VIDEO ANIMASI BERMUATAN TRI HITA KARANA PADA METERI TEKS FABEL KELAS IV SEKOLAH DASAR - Nia Charolin, Ni Komang Ameilya; Ni Made Ignityas Prima Astuti; Nyoman Ayu Putri Lestari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Animated video media containing Tri Hita Karana on fable text material for fourth grade elementary school students was developed in this study. The basis for implementing this research is the still low conventional learning methods, lack of student motivation, the absence of character values ​​such as Tri Hita Karana and the lack of optimization of the use of digital media. This study uses a Research and Development (R&D) approach with the ADDIE model. The model consists of five systematic stages, namely the analysis stage (analyze), design (design), development (development), implementation (implement), and evaluation (evaluate). The research subjects were 30 fourth grade students of SD Negeri 1 Baler Bale Agung and teachers/homeroom teachers. Data were collected through interviews, questionnaires, and documentation. The results of the validation of material experts averaged a score of 95.93% with a "very valid" category, as well as 96.25% of media experts categorized as "very valid". Teacher responses to the practicality of the media reached 100% with a "very practical" category. Meanwhile, student responses to the small-scale test reached 86.44% and the large-scale test 81.16%, categorizing both as "very practical." Based on these results, the animated video containing Tri Hita Karana was declared valid, practical, and efficient in interactive learning, meeting the needs of fourth-grade elementary school students.